Impact of lifestyle on health-related quality of life among young university students: a cross-sectional study - García-Pérez-de-Sevilla, Guillermo; Pérez-Chao, Enrique Alonso; Pareja-Galeano, Helios; Martínez-Jiménez, Eva María; de-la-Plaza-San-Frutos, Marta; Sánchez-Pinto-Pinto, Beatriz; Romero-Morales, Carlos (São Paulo Medical Journal, 2021)
BACKGROUND: Lifestyle is strongly involved in the pathogenesis and progression of noncommunicable diseases, and has a great impact on quality of life. The goal of the present study was to analyze the lifestyle and body composition (BC) of young university students during the pandemic, and their relationship with health-related quality of life (HrQoL). DESIGN AND SETTING: Observational cross-sectional study conducted in the Universidad Europea de Madrid, Spain. METHODS: A total sample of 56 healthy university students was recruited. Activity, sitting time, adherence to Mediterranean diet and BC were measured. RESULTS: Regarding BC, only 5% and 10.7% of the subjects had health risk values for waist circumference and waist-to-height ratio, respectively. The mean daily sitting-time was 8.26 hours, while 19.64% of the subjects spent ≥ 10 hours per day sitting. 92.86% of the subjects complied with the World Health Organization 2020 physical activity recommendations. The mean PREDIMED score was 7.41, while 51.8% of the subjects had low adherence to the Mediterranean diet. Regarding HrQoL, 22 subjects (39.2%) and 26 subjects (46.4%) were in the lowest quintile of physical component summary and mental component summary, respectively, according to the reference values for their age range. There was a negative correlation between physical function and sitting time (r = -0.38). CONCLUSIONS: There were high levels of sedentary behavior and low HrQoL values, with a negative moderate correlation between these variables. The findings from the present study especially highlight the importance of implementing public health programs targeting reduction of sitting time among university students.